The Effect of Irradiation Methods on Biomass Yield on Mix of Corn (zea mays) and Mung Bean (Vigna radiata) with Hydroponic system - Iin Susilawati; Lizah Khairani (Unpad Press, 2023)
The objectives of this research was to find effect of irradiation methods on the production of biomass fresh weight, leaf and root dry weight on combination of mung bean and corn with hydroponic system. This research was design with experimental method using Completely Randomized Design with 2 treatmens and 9 replications. The observed of P1 = irradiation method with the sunlight for 12 hours and P2 = irradiation method with LED grow light 7. watt for 16 hours. Parameters observed were biomass fresh weight, leaf and root dry weight Data were analyzed using of two samples Independent T-tes. The result showed that biomass fresh weight and leaf dry weight of irradiation with LED higher than irradiation with the sunlight, the average’s 3155,844 g/m2, and 55,14 g/m2, but no significant effect on dry weight of root.